High-Tech Export from the V4 Countries - Structure and Factors - Judyta Lubacha-Sember (Entrepreneurial Business and Economics Review, 2013)
Objective: The purpose of this article is to verify the relation between the value of high‐tech export and the value of intellectual capital assets.